Catenane Crosslinked Mechanically Adaptive Polymer Gel. Issue 1 (10th August 2017) - Xing, Hao; Li, Zhengtao; Wu, Zi Liang; Huang, Feihe
Abstract: A new strategy is introduced to prepare an adaptive polymer gel that has a unique adaptability in response to environmental stimuli. This gel is prepared by the thiol‐ene "click" reaction between a bisvinyl [2]catenane and a poly(ethylene glycol) derivative containing multiple thiol groups. The catenane crosslinker is responsive to external stimuli due to the existence of intercomponent hydrogen bonding (IHB). The strong IHB restricts the rotation and movement of the crosslinker, giving it a rigid feature; however, the crosslinker becomes flexible when the IHB is destroyed. In consequence, the resulting gel can be reversibly switched between tough and soft states under stimulations. Abstract : A novel polymer gel is prepared by thiol‐ene "click" reaction between a bisvinyl [2]catenane and a poly(ethylene glycol) derivative containing multiple thiol groups. Due to the existence of intercomponent hydrogen bonding in the catenane crosslinker, the resulting gel exhibits a mechanically adaptive property.